Sociological Factors and Intergenerational Interactions in Academic Workplaces: Evidence from the University of Benin - Igbinomwanhia, Osasere Greg; Akaba, Jude (NIU Journal of Social Sciences, 2026)
This study explored how power dynamics and social capital shape intergenerational interactions among academic staff at the University of Benin. It addressed a clear gap in the literature, given the limited research on intergenerational relations in Nigerian universities, even as academic workplaces continue to bring together staff from multiple generations. The study adopted a mixed-methods sequential explanatory design, combining quantitative data from 500 full-time academic staff, gathered through structured questionnaires, with qualitative data from 20 purposively selected participants through in-depth interviews. It analysed the quantitative data using descriptive statistics and examined the qualitative data through thematic analysis. The findings revealed that seniority plays a major role in workplace interactions, with 59% of respondents stating that it significantly shapes how colleagues from different generations relate to one another. The study also found that more than 73% of respondents relied, at least sometimes, on colleagues from their own generation to manage workplace challenges. At the same time, 79.2% identified trust and interpersonal relationships as important for effective collaboration across generations. Overall, the study showed that while hierarchy influences authority in the academic workplace, social capital creates the conditions for cooperation. Thus, it recommended structured mentoring, more inclusive committee systems, and deliberate trust-building efforts to strengthen collaboration across generations. Keywords: Intergenerational, academic work place, interactions, University of Benin